Characterization of Sulfur and Nanostructured Sulfur Battery Cathodes in Electron Microscopy Without Sublimation Artifacts. (23rd February 2017) - Levin, Barnaby D.A.; Zachman, Michael J.; Werner, Jörg G.; Sahore, Ritu; Nguyen, Kayla X.; Han, Yimo; Xie, Baoquan; Ma, Lin; Archer, Lynden A.; Giannelis, Emmanuel P.; Wiesner, Ulrich; Kourkoutis, Lena F.; et al.
Abstract: Lithium sulfur (Li–S) batteries have the potential to provide higher energy storage density at lower cost than conventional lithium ion batteries. A key challenge for Li–S batteries is the loss of sulfur to the electrolyte during cycling. This loss can be mitigated by sequestering the sulfur in nanostructured carbon–sulfur composites. The nanoscale characterization of the sulfur distribution within these complex nanostructured electrodes is normally performed by electron microscopy, but sulfur sublimates and redistributes in the high-vacuum conditions of conventional electron microscopes. The resulting sublimation artifacts render characterization of sulfur in conventional electron microscopes problematic and unreliable. Here, we demonstrate two techniques, cryogenic transmission electron microscopy (cryo-TEM) and scanning electron microscopy in air (airSEM), that enable the reliable characterization of sulfur across multiple length scales by suppressing sulfur sublimation. We use cryo-TEM and airSEM to examine carbon–sulfur composites synthesized for use as Li–S battery cathodes, noting several cases where the commonly employed sulfur melt infusion method is highly inefficient at infiltrating sulfur into porous carbon hosts.